Phenolics and antioxidant activity of Rangpur lime (Citrus × limonia ) extracts from peels, leaves, and juice - Contador, Maycon Hudson; Marques, Jacqueline Aparecida; Pereira, Romaiana Picada (Eclética Química, 2026)
The Rangpur lime (Citrus x limonia) is a common fruit in Brazil. Although it is popular in medicine and cuisine, few investigations were conducted into the compositions and antioxidant capacities of infusions, decoctions and from the juice, leaves, and peels. The Folin-Ciocalteu reagent was used to evaluate phenolic content; aluminum chloride to measure flavonols; and sodium borohydride was used to determine flavanones. Antioxidant capacity was assessed through ABTS•+, DPPH• radical scavenging, and ferric ions reducing power. The evaluation of different extracts confirmed that ripe fruit peels contain more phenolics and flavonoids than unripe fruit peels. Furthermore, leaves decoction presents more flavonols and flavones and higher antioxidant activity than infusion and peels, both decoction and infusion. Flavonols were identified as the primary flavonoids in peel and leaf extracts, but no flavanones were found. Conversely, juices displayed a high amount of flavanones, a significant phenolic level, and the best antioxidant capabilities, the most beneficial form for widespread consumption. Further studies must identify the primary compounds in both juices and infusions.